A new species of Lyctocoridae (Hemiptera: Heteroptera: Cimicoidea) feeding on the exuded sap of Sawtooth Oak, Quercus acutissima, in Japan - Yamada, Kazutaka; Yasunaga, Tomohide; Ichikawa, Toshihide (Zootaxa, 2012)
A new species of the family Lyctocoridae, Lyctocoris ichikawai Yamada & Yasunaga sp. nov., is described from Shikoku and Kyushu, southwestern Japan. The species was found to inhabit near the sap-exuding parts on the trunk of Sawtooth Oak, Quercus acutissima Carruth. (Fagaceae). Lyctocoris ichikawai is considered to be most closely related to L. zhangi Bu & Zheng, 2001 from continental China and L. variegatus Péricart, 1969 from the Caucasus. The unique biology of the new species, including its habitat use, feeding activities, and phenology, is documented and discussed. A key is provided to distinguish among the three Japanese species of Lyctocoris.